Unraveling the heterogeneous evolution of the microstructure and texture in the thermomechanically affected zone of commercially pure titanium during friction stir processing. (1st February 2023) - Singh, Abhishek Kumar; Kaushik, Lalit; Pawar, Saurabh; Singh, Jaiveer; Das, Hrishikesh; Mondal, Mounarik; Hong, Sung-Tae; Choi, Shi-Hoon
Highlights: A heterogeneous microstructure/texture was characterized in the TMAZ of FSPed CP-Ti. Multiple fibers textures and deformation texture components were observed in TMAZ. Inconsistent evolution of DRX mechanisms, L i j p and twin variants were observed. High activity of prismatic and basal slips was evident throughout TMAZ-II. The texture was modified by slips and multiple TT and CT variants. Abstract: The microstructure and texture of the thermomechanically affected zone (TMAZ) in friction stir processed (FSPed) CP-Ti material was investigated via electron backscatter diffraction (EBSD), finite element analysis (FEA), and polycrystal modeling. This study aimed to characterize the complicated deformation history in TMAZ and its systematic correlation with the asymmetric deformation and dynamic recrystallization mechanisms during FSP. Microstructure observation of the TMAZ revealed two distinct regions based on grain average misorientation (GAM) criteria: TMAZ-I was characterized by a mixture of deformed, substructured, and recrystallized grains near the stir zone; and TMAZ-II was characterized by only deformed and substructured grains near the bottom section. The texture development in the TMAZ was highly dependent on its deformation history, which differed for different zones. A multi-mechanism of dynamic recrystallization (DRX) was involved in the development of the submicron grain structure in TMAZ-I. A combined study of EBSD and the visco-plastic self-consistent properties (VPSC) revealed multiple fiber textures and deformation texture components in both TMAZ-I and TMAZ-II. High levels of prismatic and basal slip activity were observed throughout TMAZ-II. The texture of the zones was modified by tension twins and slips in the retreating side (RS) and the central zone (CZ) of TMAZ-II, while compression twins and slips were mainly responsible for the texture in the advancing side (AS). The inconsistent evolution of the DRX mechanism, velocity gradient components, and multiple tension and compression twin variants in various regions caused the development of the heterogeneous microstructure, texture, and hardness. Graphical abstract: Image, graphical abstract